Analysis of Critical Thinking Skills in Reaction Rate Using Guided Inquiry with Web-Assisted Courses - Ayu Indahyana; Harun Nasrudin (FKIP University of Mataram, 2021)
This research aims to describe the result of the analysis students` critical thinking skills through the implementation of guided inquiry learning models with web-assisted courses in reaction rate. The subject is students` XI MIPA 2 SMAN 1 Taman. The type of this research is pre-experimental design with one group pretest-posttest design. This research uses observation, test and questionnaire methods. The instruments used are a sheet of the critical thinking skills test, observation sheet of learning model implementation, activity observation sheet, and student response questionnaire sheets. Quantitative methods with SPSS 23 to analyze this research data. The result of this research showed that (1)The percentage of learning model implementation at the first and second meetings are 98,06% (very good) and 99,07% (very good). (2)The relevant activities of student's at the first and second meetings are 98,47% and 97,84%. (3) Students' critical thinking skill is successfully trained with the average gain score on the interpretation indicator is 0.90 (high), inference indicator is 0,93 (high), analysis indicator is 0,90 (high) and explanation indicator is 0,89 (high). (4)The positive response of students` is 91.18%. The results showed that the guided inquiry learning model with web-assisted courses in reaction rate material could improving students' critical thinking skills.